Synthetic Study of 5‐Hydroxymethylfurfural in Groebke‐Blackburn‐Bienaymé Reaction. Issue 10 (8th February 2022) - de la Sovera, Victoria; López, Gloria V.; Porcal, Williams
Abstract: In the present study, we explored the reactivity of 5‐hydroxymethylfurfural (5‐HMF), a renewable platform chemical, as the aldehyde component in the Groebke‐Blackburn‐Bienaymé (GBB) multicomponent reaction. Given the limited stability of 5‐HMF under conventional conditions used for this reaction, acidic milieu in combination with high temperature or long reaction times, we explored factors which influence the course of the reaction (solvent, catalyst, time, and temperature) within the guidelines of previously reported green reaction conditions. Mild conditions and short reaction times were achieved to obtain good conversion and selectivity values. The reaction scope was exemplified by preparing a small compound library based on the optimized conditions varying the amidine and the isocyanide component. The hydroxymethylfuran moiety present in the GBB products, imidazo[1, 2‐a]heterocycles, provides useful functionalization for further transformations, which could expand the diversity of the chemical space. Abstract : The use of renewable 5‐hydroxymethylfurfural as the aldehyde component in the GBB multicomponent reaction was explored. Mild conditions and short reaction times were achieved to obtain new imidazoheterocycles with good selectivity. A small compound library based on the optimized conditions was built to exemplify the scope.